Vegetation analysis of 10 urban forests in the city of Banda Aceh, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Dharma W, Zakaria R. 2022. Vegetation analysis of 10 urban forests in the city of Banda Aceh, Indonesia. Biodiversitas 23: 4131-4137. The vegetation of urban forests is strongly influenced by the composition of trees planted in the forest area. In order to maintain its sustainability, complete vegetation data is needed as a basis for good urban forest management. The purpose of this study was to identify the species diversity of trees in 10 urban forests in the city of Banda Aceh. The study was conducted using the Cruising method with the count of all vegetation species found in urban forests in the city of Banda Aceh. Data analysis was done by the vegetation analysis method through the calculation of diversity index (H'), Relative Frequency (RF), Relative Density (RD), Relative Dominance (RB), and Importance Value Index (IVI). The results showed that the tree component of the area was composed of 50 tree species representing 2218 individuals. The highest IVI value was found in Samanea saman with an IVI value of 67.95, and the lowest was in Tamarindus indica species with an IVI value of 8.16. The diversity index in the observed urban forests was low, with the highest index in Tibang forest at only 0.37. In order to increase plant diversity in urban forests in the city of Banda Aceh, plant species enrichment is needed. It is expected to increase ecological functions in the surrounding environments.